Meaning versus Grammar An Inquiry into the Computation of Meaning and the Incompleteness of Grammar - Cremers, Crit (Leiden University Press, 2014)
This volume investigates the complicated relationship between grammar, computation, and meaning in natural languages. It details conditions under which meaning-driven processing of natural language is feasible, discusses an operational and accessible implementation of the grammatical cycle for Dutch, and offers analyses of a number of further conjectures about constituency and entailment in natural language.